2021
DOI: 10.3389/fmed.2021.621592
|View full text |Cite
|
Sign up to set email alerts
|

A Low Albumin-to-Globulin Ratio Predicts a Poor Prognosis in Patients With Metastatic Non-small-cell Lung Cancer

Abstract: Objective: The serum albumin-to-globulin ratio (AGR) may be a useful prognostic factor for various cancers. This study aimed to evaluate the prognostic value of the AGR in patients with metastatic non-small-cell lung cancer (NSCLC).Methods: A retrospective study was conducted on patients with stage IV NSCLC diagnosed in Hubei Cancer Hospital from July 2012 to December 2013. The formula for calculating the AGR was serum albumin/total protein-serum albumin. The chi-square test or Fisher's exact test was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…As one of the main cortisol‐binding proteins, globulin would increase with the accumulation of acute phase proteins and participated in immune and inflammatory responses. It was reported that AGR can serve as an independent prognostic indicator for non‐small cell lung cancer (NSCLC), lymphoma, and gastric cancer 33–35 . Zhou 36 showed that AGR was an independent negative factor for predicting OS of SCLC patients (our study showed a similar result).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…As one of the main cortisol‐binding proteins, globulin would increase with the accumulation of acute phase proteins and participated in immune and inflammatory responses. It was reported that AGR can serve as an independent prognostic indicator for non‐small cell lung cancer (NSCLC), lymphoma, and gastric cancer 33–35 . Zhou 36 showed that AGR was an independent negative factor for predicting OS of SCLC patients (our study showed a similar result).…”
Section: Discussionsupporting
confidence: 78%
“…It was reported that AGR can serve as an independent prognostic indicator for non-small cell lung cancer (NSCLC), lymphoma, and gastric cancer. [33][34][35] showed that AGR was an independent negative factor for predicting OS of SCLC patients (our study showed a similar result). Meanwhile, we also found AGR was significant in the univariate analysis of PFS.…”
Section: F I G U R E 1 Os Curves Of Sclc In the Training (A) And Vali...supporting
confidence: 81%
“…Clinical data and laboratory data were collected using routine blood tests for fibrinogen (Fib), white blood cells (WBC), neutrophils (N), lymphocytes (L), monocytes (M), D dimer (D-D), platelets (PLT), hemoglobin (Hb), albumin (ALB), globulin (GLB), prealbumin (PAB) within 1 week before diagnosis. The ratio of albumin to globulin (AGR) ( 18 ), NLR, derived neutrophil to lymphocyte ratio (dNLR) ( 19 ), PLR, LMR, MLR, OPNI, SII, and SIRI were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…These globulins are produced by either the liver or by components of the immune system and are critical in the immune response and chronic inflammation. Globulin has been investigated as part of the albumin/globulin ratio (albumin/total), which predicts long-term survival in early and late-stage NSCLC settings [48][49][50].…”
Section: Albuminmentioning
confidence: 99%